2019
DOI: 10.1177/1362361319857375
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported social impairments predict depressive disorder in adults with autism spectrum disorder

Abstract: In adults with autism spectrum disorder, co-occurring psychiatric conditions are prevalent, and depression is one of the most common co-occurring disorders. This study examined the relationship between depression and cognitive ability, autism symptom severity, and self-reported social impairments in autism spectrum disorder. A total of 33 adults with autism spectrum disorder and 28 adults with typical development completed a standardized psychiatric interview, cognitive test, measure of clinician-rated autism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…The development of screening tools that evaluate subjective social experiences for this population may thus be an important step in identifying those at risk for depression. Social experiences play a significant role in the manifestation of depression for individuals on the autism spectrum (Day et al, 2019). While negative social experiences can be a risk factor for depression, we found that positive social experiences can serve as protective factors in preventing depressive symptomatology by leading to positive affect.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…The development of screening tools that evaluate subjective social experiences for this population may thus be an important step in identifying those at risk for depression. Social experiences play a significant role in the manifestation of depression for individuals on the autism spectrum (Day et al, 2019). While negative social experiences can be a risk factor for depression, we found that positive social experiences can serve as protective factors in preventing depressive symptomatology by leading to positive affect.…”
Section: Discussionmentioning
confidence: 57%
“…Social experiences play a significant role in the manifestation of depression for individuals on the autism spectrum (Day et al, 2019 ). While negative social experiences can be a risk factor for depression, we found that positive social experiences can serve as protective factors in preventing depressive symptomatology by leading to positive affect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…impairments in social functioning, may act as risk factors for mental health comorbidities. For instance, more severe social impairment, poorer social skills, and higher self-perceived social incompetence have been associated with increased depression symptoms in children, adolescents, and adults with ASD (Chang et al, 2012;Day et al, 2020;Duan et al, 2020;Pouw et al, 2013;Vickerstaff et al, 2007). However, there remains a gap in our knowledge regarding how individual characteristics confer risk for mental health outcomes in different contexts for individuals with ASD.…”
mentioning
confidence: 99%